Studi Perilaku Harian Rusa Timor (Cervus timorensis) Di Penangkaran Rusa Universitas Lampung - Bainah Sari Dewi; Siti Neneng Nurjanah; Dian Iswandaru; Sugeng P. Harianto (University of Lampung, 2024)
University of Lampung is one of the institutions that support the conservation of timor deer (Cervus timorensis) through ex-situ conservation in the form of captivity. In an effort to develop timor deer in captivity, it is necessary to know the daily behavior data. The purpose of this study was to determine the daily behavior of timor deer in deer breeding at Lampung University. This research was conducted for 10 days in October-November 2023, starting at 06.00-18.00 WIB. The method used was the scan sampling method, and the object of research was 11 individual timor deer. The results show that timor deer perform eating behavior with a percentage of 47.38%, rest 34.94%, move 16.59%, sharpen antlers 0.18%, hole 0.15%, and other behaviors 0.72%.